An axoplasmic myosin with a calmodulin-like light chain. - Bearer, E L (1996)
Organelles in the axoplasm from the squid giant axon move along exogenous actin filaments toward their barbed ends. An approximately 235-kDa protein, the only band recognized by a pan-myosin antibody in Western blots of isolated axoplasmic organelles, has been previously proposed to be a motor for these movements. Here, we purify this approximately 235-kDa protein (p235) from axoplasm and demonstrate that it is a myosin, because it is recognized by a pan-myosin antibody and has an actin-activated Mg-ATPase activity per mg of protein 40-fold higher than that of axoplasm. By low-angle rotary shadowing, p235 differs from myosin II and it does not form bipolar filaments in low salt. The amino acid sequence of a 17-kDa protein that copurifies with p235 shows that it is a squid optic lobe calcium-binding protein, which is more similar by amino acid sequence to calmodulin (69% identity) than to the light chains of myosin II (33% identity). A polyclonal antibody to this light chain was raised by using a synthetic peptide representing the calcium binding domain least similar to calmodulin. We then cloned this light chain by reverse transcriptase-PCR and showed that this antibody recognizes the bacterially expressed protein but not brain calmodulin. In Western blots of sucrose gradient fractions, the 17-kDa protein is found in the organelle fraction, suggesting that it is a light chain of the p235 myosin that is also associated with organelles.